Problems of Performance of Contractual Obligations Due to War Time - Dikovska, Iryna (Teisė, 2024)
The paper aims to elucidate the legal consequences of the impossibility or hardship of performing contracts due to war or circumstances caused by war under the laws of Ukraine, Germany and Switzerland. Since in all the jurisdictions studied they can be determined by both contractual and legislative provisions, the paper first focuses on the interpretation of force majeure clauses under the laws of Ukraine, Germany and Switzerland. It also analyzes what consequences of the impossibility of performing a contract due to war or circumstances caused by war may arise when the contract does not define them.
Keywords: contractual performance; force majeure; war; sanctions; martial law; restrictions of export of goods; interpretation of contracts